Novel Insights into How Overnutrition Disrupts the Hypothalamic Actions of Leptin - Fruhwürth, Stefanie; Vogel, Heike; Schürmann, Annette; Williams, Kevin Jon (Frontiers in Endocrinology, 2018)
Obesity has become a worldwide health problem, but we still do not understand the molecular mechanisms that contribute to overeating and low expenditure of energy. Leptin has emerged as a major regulator of energy balance through its actions in the hypothalamus. Importantly, obese people exhibit high circulating levels of leptin, yet the hypothalamus no longer responds normally to this hormone to suppress appetite or to increase energy expenditure. Several well-known hypotheses have been proposed to explain impaired central responsiveness to the effects of leptin in obesity, including defective transit across the blood-brain barrier at the arcuate nucleus, hypothalamic endoplasmic reticulum stress, maladaptive sterile inflammation in the hypothalamus, and overexpression of molecules that may inhibit leptin signaling. We also discuss a new explanation that is based on our group’s recent discovery of a signaling pathway that we named “NSAPP” after its five main protein components. The NSAPP pathway consists of an oxide transport chain that causes a transient, targeted burst in intracellular hydrogen peroxide (H2O2) to inactivate redox-sensitive members of the protein-tyrosine phosphatase gene family. The NSAPP oxide transport chain is required for full activation of canonical leptin signaling in neurons but fails to function normally in states of overnutrition. Remarkably, leptin and insulin both require the NSAPP oxide transport chain, suggesting that a defect in this pathway could explain simultaneous resistance to the appetite-suppressing effects of both hormones in obesity.